MEASUREMENT STAND FOR STUDY PROPERTIES OF ISOLATION MATERIALS USING POLARIZATION METHOD - P. Zukowski; T. Koltunowicz; Cz. Kozak; K. Kierczynski; P. Rogalski (Приборы и методы измерений)
The article presents measurement stand, which is used to measure polarization and depolarization currents, using PDC method, in wet transformer oil-impregnated cellulose isolation. Maximum resolution of measured currents reaches 10-15  A. The accuracy of thermal stabilization, in three-electrode capacitor system, comes to 0,001 °C.